Student unrest at black universities in Southern Africa, with special reference to the University of the North, 1960-1990 - Mphahlele, Sentsho Ernest (My University, 1992)
Refer to the document
Thesis (Ph.D. (Education)) -- University of the North, 1992
Keywords: Student unrest; Black universities; Universities and colleges, Black -- South Africa